The Performance of Certified Educator Teachers in Managing Learning - Tifa Sri Fanora; Murniati Murniati; Bahrun Bahrun (STAI Hubbulwathan Duri, 2022)
This study aimed to determine the performance of certified teacher teachers in managing learning at a Private Madrasah Aliyah in Banda Aceh. The approach used in this research is qualitative. The type of research used in this research is descriptive. The results showed that the performance of certified teachers in managing learning had been made as much as possible so that it is carried out as expected. The supporting factors for the performance of certified educator teachers in managing learning consist of internal and external factors. Internal factors that hinder the learning process are influenced by the lack of experimental materials provided in the laboratory.